OPTIMALISASI MANAJEMEN MUTU TERPADU DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN ISLAM BERBASIS TEKNOLOGI - Badrut Tamam; Sudadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of digital technology has brought significant changes in the development of Islamic education curricula. The use of technologies such as e-learning, Learning Management Systems (LMS), digital learning media, and artificial intelligence provides opportunities for Islamic educational institutions to improve the quality of learning to make it more effective, innovative, and adaptive to the needs of the 21st century. However, digital transformation also presents various challenges, such as low digital competence of educators, limited technological facilities and infrastructure, and the potential decline in students' moral and spiritual values ​​due to unwise use of technology. This study aims to analyze the optimization of Total Quality Management (TQM) in the development of a technology-based Islamic education curriculum. The study used a literature review method with a descriptive qualitative approach through analysis of various relevant literature sources. The results show that the implementation of TQM can support curriculum quality improvement through strengthening teacher competencies, integrating technology with Islamic values, involving all stakeholders, and implementing continuous evaluation and improvement. Thus, optimizing TQM can produce an Islamic education curriculum that is adaptive to technological developments without neglecting the goal of developing students' character and morals.